Metaheuristic Algorithms for Healthcare: Open Issues and Challenges. (July 2016) - Tsai, Chun-Wei; Chiang, Ming-Chao; Ksentini, Adlen; Chen, Min
Highlights: A brief survey of metaheuristics for healthcare system is given. A learnable big data analytics framework for healthcare system is presented. Open issues and future trends of metaheuristics for healthcare system are addressed. Graphical abstract: Abstract: Inspired by the observation that a healthcare system usually involves various intelligent technologies from different disciplines, especially metaheuristics and data mining, this paper provides a brief survey of metaheuristics for healthcare system and a roadmap for researchers working on metaheuristics and healthcare to develop a more efficient and effective healthcare system. This paper begins with a discussion of changes for healthcare, followed by a brief review of the features of "up-to-date technologies for healthcare.". Then, a learnable big data analytics framework for healthcare system is presented which provides a high performance solution to the forthcoming challenges of big data. Finally, changes, potentials, open issues, and future trends of metaheuristics for healthcare are addressed.